3D Tomographic Imaging of P Wave Velocity Structure Beneath Java Island using Fast Marching Tomography Method - Uswatun Chasanah; Bagus Jaya Santosa (IPTEK Journal of Science, 2017)
Java Island one of the best locations for geophysics research, as it’s located near the edge of the junction of continental Eurasia Plate and the Indo-Australia Plate with the movement of the plates 6 cm/year. Its needed the accurate imaging of subsurface structure to understanding complex tectonic setting. The first arrival time from local earthquake of Java (6,360-9,150 S and 105,890-115,540 E) with magnitude greater than 4,5 Mw occurred from 2011 until 2013 recorded by local network seismograph has been inverted for three dimensional variation of the depth to the P wave velocity in the Java island. At the same time, earthquake hypocenter location has been corrected simultaneous. This research apply a new tomographic inversion scheme FMTOMO that has been developed by Rawlinson (2004).  The results of inversion show that there are three layer in 100 km from the surface at continental plate side (Eurasia). The continental upper crust has P wave velocity variation about 4-5,5 km/s in the depth until 30 km from the surface. There are low velocity anomaly inclined towards the slab which probably have associated with shallow earthquake along the slab